TINGKAT KEPUASAN PEMIRSA TELEVISI DI DENPASAR TERHADAP TAYANGAN BERITA DI METRO TV - Monangin, Tesalonika; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 1 (2020): Jurnal Ilmu Komunikasi 2020, 2020)
ABSTRACT   Metro TV is the first television channel in Indonesia that take the news as their main program. KPI survey has told us that the quality of Metro TV news is in good quality standard. The theory uses and gratification use as the main theory, and theory of social responsibility is the support theory. This research uses the quantitative descriptive method that collected data and to descript the result. To found the sample, this research will use random sampling and the question method is the close questionnaire. The result of this research will be attributed to aspects of the uses and gratification theory. When watching Metro TV news, the Denpasar audiences feel fulfilled of the aspects that in uses and gratification theory, the conclusion is Denpasar audiences feel satisfied with Metro TV news that KPI says is one of the TV channels that have qualified quality standard. Key Word: Metro TV, News, Uses and Gratification Theory, Quantitative Descriptive